2016
DOI: 10.1016/j.ejrad.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of actionable findings on contrast enhanced magnetic resonance angiography ordered for pulmonary embolism evaluation

Abstract: MRA as a first-line test for PE can identify actionable findings in those patients without PE, with an incidence similar to that reported in the literature for CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The rate of clinically significant IFs in our study was not different from that of a previous similar study, which identified actionable, incidental findings in 21.5% of patients receiving acute stroke intervention combined with CTA of the head and neck. [ 2 ] This might be expected, as we found some IFs, that is, pulmonary embolism, which were not reported before, even though our data of neck CTA cases have smaller coverage and fewer images.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The rate of clinically significant IFs in our study was not different from that of a previous similar study, which identified actionable, incidental findings in 21.5% of patients receiving acute stroke intervention combined with CTA of the head and neck. [ 2 ] This might be expected, as we found some IFs, that is, pulmonary embolism, which were not reported before, even though our data of neck CTA cases have smaller coverage and fewer images.…”
Section: Discussionsupporting
confidence: 61%
“…With the rapid technological advance in image acquisition and spatial resolution, computed tomographic angiography (CTA) serves increasingly as a quick, accurate, and attractive noninvasive clinical procedure [ 1 , 2 ] and has largely replaced digital subtraction angiography (DSA). The latter has long been considered as standard diagnostic procedure, an imaging modality for assessing the vessels of lower extremity, [ 3 ] cardiac, [ 4 ] pulmonary artery.…”
Section: Introductionmentioning
confidence: 99%
“…The ancillary findings observed on CE-MRA exams in those patients without PE are similar to those of CTA (Figure 5 )[ 89 , 90 ]. The field of view is larger and the soft tissue contrast is better on CE-MRA exams than CTA.…”
Section: Ancillary Findingsmentioning
confidence: 58%
“…In a recent study, the incidence of actionable findings (requiring follow up) from CE-MRA exams was 17% (pleural effusion, pneumonia, malignancy, ascending aortic aneurysm, aortic dissection, pericardial effusion, heart failure, septic emboli, lung abscess, trauma, and sarcoidosis). While the incidence of incidental findings (those findings not requiring follow up) was 36% (mild dependent atelectasis, small pleural effusion, normal vascular variant, simple cysts in liver or kidney and post-surgical changes)[ 89 ].…”
Section: Ancillary Findingsmentioning
confidence: 99%
“…Dynamic Contrast Enhanced (DCE) perfusion imaging techniques using gadolinium-based contrast agents (GBCAs) have shown promise for more than a decade. Recently, translational advances have enabled the investigation of diseases such as pulmonary embolism (36,37), pulmonary hypertension (24)(25)(26), and CF in pediatric and young adult populations (38)(39)(40). In pulmonary DCE MRI contrast is injected and dynamic images are acquired prior and during the passage of the contrast bolus.…”
Section: Imaging Lung Function With Hyperpolarized 129 Xe Dce Perfusmentioning
confidence: 99%